2001
DOI: 10.1074/jbc.m101786200
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Upper Size Limit for Uptake and Processing of Ligands by the Asialoglycoprotein Receptor on Hepatocytesin Vitro and in Vivo

Abstract: The asialoglycoprotein receptor (ASGPr) on hepatocytes plays a role in the clearance of desialylated proteins from the serum. Although its sugar preference (N-acetylgalactosamine (GalNAc) > > galactose) and the effects of ligand valency (tetraantennary > triantennary > > diantennary > > monoantennary) and sugar spacing (20 Å > > 10 Å > > 4 Å) are well documented, the effect of particle size on recognition and uptake of ligands by the receptor is poorly defined. In the present study, we assessed the maximum lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
160
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(171 citation statements)
references
References 70 publications
9
160
1
Order By: Relevance
“…Ligand binding was assessed using flow cytometry to monitor the fraction of cells bound to biotinylatedGalNAc as a function of ligand concentration The calculated Kd values for the bi-and triantennary GalNAc were 28.3 and 2.3 nM respectively, consistent with binding affinities obtained for radiolabeled ligand-receptor assays previously reported where calculated Kd values were 4.3 nM for GalNAc 3 and 25 nM for a bi-antennary ligand (GalNAc 2 ) (Connolly et al 1982;Connolly et al 1983;Biessen et al 1995;Lee et al 1983;Rensen et al 2001) (Fig. 6).…”
Section: Galnac Binding As Functional Read-outsupporting
confidence: 51%
See 2 more Smart Citations
“…Ligand binding was assessed using flow cytometry to monitor the fraction of cells bound to biotinylatedGalNAc as a function of ligand concentration The calculated Kd values for the bi-and triantennary GalNAc were 28.3 and 2.3 nM respectively, consistent with binding affinities obtained for radiolabeled ligand-receptor assays previously reported where calculated Kd values were 4.3 nM for GalNAc 3 and 25 nM for a bi-antennary ligand (GalNAc 2 ) (Connolly et al 1982;Connolly et al 1983;Biessen et al 1995;Lee et al 1983;Rensen et al 2001) (Fig. 6).…”
Section: Galnac Binding As Functional Read-outsupporting
confidence: 51%
“…In addition, we developed a receptor-ligand binding assay to assess hepatocyte function. This assay (Connolly et al 1982: Connolly et al 1983Biessen et al 1995;Lee et al 1983;Rensen et al 2001). In addition, we demonstrated that the binding of the GalNAc ligand led to cellular uptake and gene silencing when attached to an ApoB-targeting siRNA.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Many efforts have been dedicated to the targeted delivery of drugs and genes in particular to hepatocytes by the development of galactosylated polymeric or lipid carriers in order to enhance the therapeutic effects (in case of hepatocellular carcinoma, viral hepatitis or gene-based therapies) or to reduce side-effects of drugs (in case of antiviral or anticancer drugs) (Poelska et al, 2012). Galactosylation is a speculated strategy in this field because targeting via galactosylated carriers exploit highly specific interactions of galactose ligands with endogenous lectin receptors such as asialoglycoprotein receptor (ASGPR), which is specifically and abundantly present on hepatocytes (Jain et al, 2012;Rensen et al, 2001;Wu et al, 2004). This receptor has been used to deliver to hepatocytes all kinds of therapeutic compounds ranging from therapeutic proteins, antiviral agents (Di Stefano et al, 1997) to anticancer drugs (Di Stefano et al, 2006;Fiume et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Liquorice is having two main bioactive chemical constituents named as glycyrrhizin (GL) and glycyrrhetinic acid (GA) which are widely used in medicine for the treatment of many disorders (Rensen et al, 2001;Wu et al, 2002). These are mainly used as anti-inflammatory, antiallergic, antigastric, antihepatitis and antihepatotoxic effects.…”
Section: Glycyrrhetinic Acid Ligandmentioning
confidence: 99%